Examination of Establishment of Psychological Contract of Foreign Manager in Hong Kong Foreign News Bureau with Local Employee - Vincent Hing-Po Lam (RIRAI Publisher, 2021)
This paper is to examine the news bureau chief role as the principal agency of organization to form psychological contract with local employee of Hong Kong-based foreign news bureau. The research fills the gap of current literature which focuses on Hong Kong local news’ company as the team manager does not necessarily become a party for the organization to form psychological contract with because staff can have day to day contact with the company. This research conducts 10 staff working for foreign news agency with less than 10 total employee and their line manager is the only agent contact with the parent company.